Pengaruh Endorsement Non-Selebrity Dalam Membangun Citra Merek Produk Usaha Mikro Kecil Menengah (UMKM) Dengan Eptic Model Sebagai Variabel Moderasi Di Kota Metro - Anggylia Eka Saputri; Selamet Fuadi; Ratmono (Universitas Muhammadiyah Metro, 2025)
This research used descriptive quantitative approach which the aims to determine there is aninfluence of non-celebrity endorsements in building brand image on UMKM products inMetro city. The samples in this research used 466 UMKM actors in food products. Theresults of the analysis show that non-celebrity endorsements have a significant effect onUMKM business products in the Metro city with a significance value of 0.040 which means<0.05, brand image has a significant effect on UMKM business products in the Metro citywith a significant value of 0.040 which means <0.05, eptic variable the model as amoderating variable that has a significant effect and strengthens the non-celebrityendorsement relationship on UMKM in the Metro city with t count 2.382 > than t table of(1.98397) and the eptic model variable as a moderating variable that has a significant effectand strengthens the brand image relationship on UMKM in the Metro city with t count 2.214> than t table of (1.98397).